Efficacy and cost-effectiveness analysis of steroid in treatment of Otitis Media with Effusion (OME) in children: A Randomized Trial - Acharya, Anup; Pokharel, Bandana; Pandit, Shiva Bhushan; Bartaula, Suman (Journal of Gandaki Medical College-Nepal, 2020)
Background: Otitis media with effusion (OME) is a common disorder in children and lacks international consensus for its treatment. Out of various treatment options, few studies have show promising benefits of steroids for this condition. The objective of this study was to find the efficacy of steroid in treatment of OME and compare effectiveness of various modalities of treatment for OME. Also, we conducted their cost-effectiveness analysis. Methods: In this experimental study, 160 children between one and 12 years of age having OME between September 2018 and January 2020 were randomized into four parallel groups and were managed with antibiotics-antihistamines-decongestant combination, nasal steroid spray, oral steroid, and watchful observation respectively. They were re-evaluated in one-month period for improvement in OME and appearance of any adverse effects. Improvement was compared with Chi-square test. Results: A total of 160 participants were randomly divided into four groups by block randomization. The group treated with nasal steroid spray showed statistically significant improvement. The group treated with oral steroid showed improvement but was not statistically significant. Improvement was significantly lower in observation group. Cost of treatment was in the decreasing order in antibiotics-combination, nasal steroid spray, oral steroid and observation groups respectively. Conclusions: Topical nasal steroid was the only efficacious treatment among the four modalities for OME. Furthermore, steroids were safe and cheaper than antibiotics combination.